Eficácia do uso do fio dental para tratamento da gengivite proximal em adultos: resultados parciais de um ensaio clínico randomizado cego - Londero, Ananda Barrachini (2019)
This blinded randomized clinicaltrial evaluated the efficacy of dental floss plus toothbrush, compared to toothbrushing alone, in the treatment of proximal gingivitis in adults. Forty-nine subjects, systemically healthy, without loss of proximal attachment and with generalized gingivitis at proximal sites were included in the study. Smoking subjects with fixed orthodontic braces or restraint and pregnant women were not eligible. At baseline, subjects were randomized into two groups according to the use of dental floss: Manual toothbrushing group without the use of dental floss (TB) and Group dental toothbrushing manual and dental floss (DF). For two months, the subjects attended a weekly consultation for professional plaque removal and buccal hygiene orientation. Index of Gingival Bleeding (GI) and Plaque Index (PII) at baseline, 30 and 60 days were measured by a blinded evaluator. Linear Mixed Models were used to compare the means of IPI and GI between groups. The difference in PII (p = 0.718) and GI (p = 0.612) between the groups was not significant. The means of PII and IG decreased in both groups over time. Only between the baseline period and 30 days the GI reduction was significant statistically. The reductions in PII and GI averages were observed in both groups. The disorganization of biofilms by the multitufde toothbrush when performed efficiently achieves results similar to those observed when in addition to brushing individuals also used dental floss.